The Effect Of Puzzle Media-Assisted Discovery Learning Model On Students' Conceptual Understanding Of Fraction Material In Grade VII - Evi Lesda Yanti Ginting; Simon M. Panjaitan; Sanggam P. Gultom (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The purpose of this research was to analyze the effects on seventh graders' conceptual knowledge of fractions during the 2025–2026 school year at SMP Negeri 1 Namorambe using a discovery learning strategy based on puzzles. The technique employed a quasi-experimental approach with two groups of students chosen at random from clusters: one group served as an experimental unit with 34 students, while the other group served as a control unit with 35 students. Unlike the control group, who received traditional instruction, the experimental group used a puzzle-assisted discovery learning paradigm. The data was gathered via observation sheets and essay exams. The findings of the data analysis showed that at a significance level of 5%, the model had a substantial impact on students' conceptual knowledge, as shown by a Sig. (2-tailed) value of 0.00 < 0.05. Students' conceptual knowledge was enhanced to 37.4% using” the puzzle-assisted discovery learning technique